Assessment of preventive fungicide applications for control of gray snow mold diseases in Windsor, VT, 2023-2024 - Soonhong Min; Jaime C. Piñero (Plant Health Progress, 2026)
Grey snow mold, caused by Typhula incarnata, is a prevalent turfgrass disease that develops under extended periods of snow cover combined with cool, wet conditions. Symptoms include large matted patches of grey or straw-colored turf that become evident after snowmelt, often leading to significant turf damage. Signs of the disease include dense grey mycelium on infected plants and the formation of small, pink sclerotia within affected tissue. This study evaluates the efficacy of various chemical treatments in managing grey snow mold on Agrostis stolonifera and Poa annua mixed turf during the 2023–2024 season in Vermont. The findings provide practical insights for turfgrass managers and golf course superintendents seeking effective disease control strategies.